1996
DOI: 10.1002/j.1460-2075.1996.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Rho guanine nucleotide dissociation inhibitor protein (RhoGDI) inhibits exocytosis in mast cells.

Abstract: Introducing non‐hydrolysable analogues of GTP into the cytosolic compartment of mast cells results in exocytotic secretion through the activation of GTP binding proteins. The identity and mechanism of action of these proteins are not established. We have investigated the effects of Rho GDP dissociation inhibitor (RhoGDI) on exocytosis induced by guanosine 5′‐O‐(3‐thiotriphosphate) (GTP‐gamma‐S) in rat mast cells, introducing the protein into cells by means of a patch pipette and recording the progress of exocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…We showed that the interaction between RalA GTPase and the exocyst is critical for GTP-dependent exocytosis. The involvement of other GTPases (Rab3A and Rho) in GTP-dependent exocytosis has been previously suggested (12,15). The experiments using the Rab3A fragment (effector loop peptide) in mast cells (15) are now being questioned because the fragment induces Ca 2ϩ transients in mast cells, raising the possibility that its mode of action is nonspecific (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the interaction between RalA GTPase and the exocyst is critical for GTP-dependent exocytosis. The involvement of other GTPases (Rab3A and Rho) in GTP-dependent exocytosis has been previously suggested (12,15). The experiments using the Rab3A fragment (effector loop peptide) in mast cells (15) are now being questioned because the fragment induces Ca 2ϩ transients in mast cells, raising the possibility that its mode of action is nonspecific (52).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the Rho, Rab, and Ral families of low molecular weight proteins, which are monomeric GTPases, have been suggested as regulators of exocytosis. Rho family proteins have been proposed to regulate exocytosis in mast cells (10), because Rho GDP dissociation inhibitor (RhoGDI) (11) has been shown to inhibit GTP␥S-induced exocytosis in mast cells (12). RhoGDI is known to inhibit GDP/GTP exchange in Rho family proteins including Rho, Cdc42, and Rac (11,13,14).…”
mentioning
confidence: 99%
“…For instance, Rho GDIa caused disappearance of stress ®bers and inhibition of cell motility in Swiss 3T3 cells and 308R mouse keratinocytes (Miura et al, 1993;Takaishi et al, 1993Takaishi et al, , 1994, aected the localization of the ERM (Ezrin, Radixin, Moesin) family proteins and vinculin at the plasma membrane in MDCK cells . Exocytosis from rat mast cells (Mariot et al, 1996) and PC12 cells (Komuro et al, 1996) was inhibited by Rho GDIa, whereas receptor-mediated endocytosis of transferrin was suppressed by Rho and Rac but restored by Rho GDIa (Lamaze et al, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies indicate that Rho GTPases are also involved in activation of RBL cells (18 -21). For example, stable expression of dominant negative Rac and Cdc42 in RBL cells inhibited Fc⑀RI-mediated degranulation (22), and RhoGDI, a guanine nucleotide dissociation inhibitor that was shown to block the biological activity of Rho GTPases, inhibited regulated exocytosis from RBL cells (23).…”
mentioning
confidence: 99%